Konsep PAUD dalam Quran dan Hadist - Mujahid, Kasori; Hadiwijaya, Lalu Firman (TSAQOFAH, 2025)
Early childhood education (ECE) from an Islamic perspective has a strong foundation in the Quran and Hadith. This study aims to comprehensively examine the concept of ECE in these two primary sources of Islamic teachings and its implications for contemporary educational practices. Using a literature review method with a qualitative approach, this research analyzes Quranic verses, Hadith, and related literature to identify the fundamental principles of early childhood education in Islam. The findings reveal that the concept of ECE in the Quran and Hadith is built upon three main pillars: tawhid (monotheism), akhlaq (morality), and ilm (knowledge), with educational methodologies including uswah (modeling), tadarruj (gradualism), hiwar (dialogue), qishshah (storytelling), and mumārasah (practice). The implementation of this concept in modern ECE settings shows significant improvements in spiritual-moral development (72%), socio-emotional development (67%), and language development (56%). These findings confirm the relevance and effectiveness of a Quran and Hadith-based approach in developing contemporary ECE programs.